ANALYSIS OF DEMAND FOR TRUNK FISH (Euthynnus affinis) IN NORTH PADANG DISTRICT. PADANG CITY - Dicky Rustam; Siti Aisyah (Berkala Perikanan Terubuk, 2023)
Consumer taste is one of the factors that can influence consumer demand for an item. The consumer's taste or taste for Tongkol fish (the smell and taste of Tongkol fish) will also influence the size of consumption and demand for Tongkol fish. Consumer tastes can be identified by looking at consumer preferences, consumer perceptions and consumer awareness. This research aims to analyze the influence of the price of tuna, the price of skipjack tuna, consumer income, and consumer tastes on the demand for tuna in North Padang District, Padang City. The type of research used is quantitative research using survey research methods. The analytical method used is multiple linear regression analysis, the dependent variable of this research is demand for tuna, then the independent research variables are, the price of tuna, price of skipjack tuna, consumer income and consumer tastes. The results of the research show that the variable price of tuna has a significant and negative effect on the demand for tuna in Padang Utara sub-district, Padang City, the variables of the price of skipjack tuna, income and consumer tastes have a significant and positive effect on the demand for tuna in Padang Utara sub-district, Padang City.